The of effect of partnership-based education on adherence to the treatment plans in open heart surgery - Fatemeh Bahramnezhad; Neda Sanaie; Alun C Jackson; Esmail Shariati; Foroozan Atashzadeh-Shoorideh (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Adherence to the treatment plans is one of the most effective conducts to prevent and reduce postoperative side effects. Partnership-based education is one of the most efficient ways to shape health behaviors. The aim of the present study was to determine the effect of partnership-based education on adherence to the treatment plans in open heart surgery. MATERIALS AND METHODS: This quasi-experimental study was conducted in 2019-2020 on the patients undergoing open heart surgery in Tehran (Capital of Iran). Sampling was done in one educational hospital. A total of 86 patients and their caregivers participated in the study. Sampling was done nonrandomly by tossing a coin, and patients were allocated into the odd week in the intervention group and the even week in the control group (n = 43 in each group), and data were collected before and after intervention using the Treatment Adherence Questionnaire concerning dietary, physical activity, and medication aspects. The educational intervention was carried out after the pretest analysis in five 20-45 min sessions (two individual and three group educations). Data were analyzed with Chi-square, independent t-test, and paired t-test using SPSS 19 at a significance level of P < 0.05. RESULTS: Patients and caregivers in both groups did not have a significant difference in terms of demographic variables (P > 0. 05). In addition, there was no significant difference in the mean of dietary, physical activity, and medication plans before the intervention in both groups; however, after the intervention, the mean of the three aspects in the intervention group was significantly higher than that of control (P < 0.001). CONCLUSION: Implementing partnership-based education with participation of patients and caregivers is influential in improving patients' adherence to the treatment plans and it is recommended as a clinical dynamic educational strategy.